Crystallisation regulation of long‐chain branched polypropylene on dielectric performance and energy density for metallised film capacitors - Meng Xiao; Mengdie Zhang; Boxue Du (High Voltage, 2023)
Abstract The degradation of dielectric properties of polypropylene (PP) at high temperature affects the operational stability of metallised film capacitors. This study presents a method to improve the high‐temperature dielectric performance of PP through long‐chain branching modification and regulating the crystalline properties. Different amounts of nucleating agents were added to long‐chain branched polypropylene (LCBPP) to study the effect of crystallisation on electrical properties. The results show that the long‐chain branches improve thermal stability by enhancing the chain entanglement, and also increase the number of crystals due to heterogeneous nucleation. The addition of nucleating agents promotes the crystallisation of LCBPP, which increases the nucleation density and improves the crystallinity. The regulation of the microstructure of PP suppresses the relaxation of the chains and limits the charge transport. The dielectric constant of the modified films with long‐chain branching is slightly increased, and the doping of nucleating agents has little effect on the dielectric constant and loss of LCBPP. At 125°C, the conductivity of the modified LCBPP films with the addition of 0.05 wt% nucleating agent decreased by 2 orders of magnitude and the breakdown strength increased by 26.3%. This study has implications for improving the dielectric properties of PP films.